PENGARUH HARGA DAN KEPRIBADIAN MEREK TERHADAP NIAT BELI DENGAN CITRA MEREK SEBAGAI VARIABEL MEDIASI: STUDI PADA PENGGUNA PRODUK SCARLETT WHITENING - Purnomo, Hari; Raharjo, Raharjo (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study analyzes the influence of price and brand personality on purchase intention with brand image as a mediating variable among Scarlett Whitening product users. The research uses quantitative methods with PLS-SEM analysis on 120 respondents who meet the criteria of being at least 17 years old and having used Scarlett Whitening products. The results show that price and brand personality have positive and significant effects on both brand image and purchase intention, while brand image has a positive but not significant effect on purchase intention. These findings indicate that price perception and brand personality play important roles in shaping consumer purchase intention. The research model proves valid in explaining consumer behavior towards Scarlett Whitening products